The expectation hypothesis of the term structure of very short-term rates: Statistical tests and economic value☆ - DELLACORTE, P; SARNO, L; THORNTON, D (Journal of Financial Economics, 2008)
This paper reexamines the validity of the expectation hypothesis (EH) of the term structure of US repo rates ranging in maturity from overnight to 3 months. We extend the work of Longstaff [2000b. The term structure of very short term rates: new evidence for the expectations hypothesis. Journal of Financial Economics 58, 397–415] in two directions: (1) we implement statistical tests designed to increase test power in this context; (2) more important, we assess the economic value of departures from the EH based on criteria of profitability and economic significance in the context of a simple trading strategy. The EH is rejected throughout the term structure examined on the basis of the statistical tests. However, the results of our economic analysis are favorable to the EH, suggesting that the statistical rejections of the EH in the repo market are economically insignificant.